Evaluation of Original and Modified APC-Resistance Tests in Unselected Outpatients with Clinically Suspected Thrombosis and in Healthy Controls - Svensson, Peter J; Zöller, Bengt; Dahlbäck, Björn (Thrombosis and Haemostasis, 1997)
APC-resistance is the most common hereditary condition associated with venous thrombosis. It is in a majority of cases due to a single point mutation in the factor V gene (FVR506Q). Currently used functional APC-resistance tests have 85-90% sensitivity and specificity for the FVR506Q mutation. A modified test which includes predilution of patient plasma in factor V depleted plasma has increased the sensitivity and specificity for the factor V mutation. However, neither the original nor the modified APC-resistance test have been evaluated in patients with acute thrombotic events. We have therefore used the original and the modified APC-resistance tests in 220 patients with clinically suspected acute deep venous thrombosis and in 278 healthy controls. The FVR506Q mutation was determined in all patients. The patients were classified as either DVT (deep venous thrombosis)-negative or DVT-positive depending on the outcome of contrast phlebography. In individuals with normal factor V genotype, the original APC-resistance test gave significantly lower APC-ratio values both in DVT-positive and DVT-negative patients than in healthy controls. The specificity of the original APC-resistance test for the FVR506Q mutation in controls and in DVT-negative and DVT-positive patients were 85%, 54% and 28%, respectively, when a cut off APC-ratio of 3.2 which insured 100% sensitivity was used. Using the modified APC-resistance test, essentially no difference in APC-ratios between patients with normal factor V genotype and healthy controls with normal factor V genotype was observed. The modified APC-resistance test had a specificity for the FVR506Q mutation of 98.8% at an APC-ratio cut off of 2.1 which ensured 100% sensitivity. The original APC-resistance test gave lower APC-ratios in women than in men and in patients with acute thrombosis as compared to controls. In conclusion, the modified APC-resistance test is highly sensitive and specific for the FVR506Q mutation. This test can be used in clinical practice as an easy to perform screening test for the FVR506Q allele. Moreover, the test performs equally well in patients with acute suspected venous thrombosis as in healthy controls.